Цивілізаційний розвиток України: сучасні виклики та можливості в просторі публічної політики - Головач, Наталія Василівна; Згалат-Лозинська, Любов Олександрівна (My University, 2021)
Висвітлені основні проблеми цивілізаційного розвитку України, визначені їх наслідки. Обґрунтовано Новий управлінський курс цивілізаційного розвитку України. Розкрито основну сутність п’яти напрямів Нового управлінського курсу: 1) ідеологія еколюдиноцентризму, як напрям поглиблення діючої демократії в контексті збільшення зусиль турботи про долю людини через сприяння її самореалізації у всіх сферах життєдіяльності; 2) послідовний перехід всіх структур державної влади до культури системного (цільового) управління, кінцевою метою функціонування яких має стати підвищення рівня самореалізації людей (кінцевий результат фіксується індексом якості життя громадян); 3) системне формування потужного фундаменту громадянського суспільства в Україні через участь громадян в щорічному оцінюванні кінцевих результатів діяльності владних структур; 4) системна модернізація національної системи освіти в контексті формування нового покоління нації, здатного самореалізуватись в різних соціумах сучасного глобалізованого інформаційно і цифронасиченого світу; 5) формування ціннісної управлінської еліти в системі освіти і процесі професійної діяльності через налагодження зворотного зв’язку в рамках системного державного управління. Визначено ідеологічний базис розбудови Нової України на основі поглиблення демократії, спираючись на людиноцентризм гуманістичної спрямованості. The relevance of the article is determined due to the fact of unsystematic movement towards the civilizational of Ukraine development. As a result, there are no real prospects for improving the situation in the future. The purpose of the article is developing of the directions of the new management course for Ukraine civilizational development. The main problems of civilization development of Ukraine are highlighted, their consequences are determined. Current methods of combating corruption in Ukraine using formal legal methods have been defined as ineffective and practically unsuccessful. Specific fitches of the Ukrainian management elite is the inability to form a harmonious cohesive society and realize the powerful potential of the country. New approaches to solving the problem are proposed in the article. The essence of the proposed strategy of Ukraine civilizational development is providing of each person self-realization promoting through whole life within the framework of universal morality and national consciousness, which determines the humanistic orientation of democracy. Substantiation of the strategy and its implementation is based on the formation of a new internal management course for Ukraine. This requires a systematic modernization of the entire government mechanism operating in the political, economic, social and cultural institutions of the country. The article substantiates the integral New Management Course of Civilizational Development of Ukraine. The essence of the "quality of life of citizens" is considered, it demonstrates the level of self-realization of human in various spheres of their life due the indicator of degree of people urgent needs satisfaction. The main essence of five directions of the New Management Course of Civilizational Development of Ukraine is revealed by: 1) ideology of eco-human centrism as a direction of deepening the current democracy in the context of increasing efforts to care for human destiny by promoting self-realization in all spheres of life; 2) consistent transition of all structures of state power to the culture of systemic (target) management, the ultimate goal of which should be to increase the level of self-realization of people (the end result is fixed by the quality of life index of citizens); 3) systematic formation of a strong foundation of civil society in Ukraine due the participation of citizens in the annual evaluation of the final results of government activities; 4) systematic modernization of the national education system in the context of the new nation generation formation, which would be able for self-realization in different societies of the modern globalized information and digital world; 5) the formation of a value management elite during the education and the professional skills activity due the feedback within the public administration system. The ideological basis for the development of New Ukraine is determined. It is based on the deepening of democracy with an emphasis on humanistic ideology of anthropocentrism.
Keywords: цивілізаційний розвиток; civilizational development; публічна політика; public policy